ChessY: A Mathematica toolbox for the generation, visualization and analysis of positional chess graphs - Rudolph-Lilith, Michelle (SoftwareX, 2019)
The game of chess is undoubtedly one of the most popular two-player strategy board games in history, enjoyed by casual players and competing celebrated professionals alike, and serves as prototype research subject in a vast variety of fields. Although a plethora of parsers on a large number of different platforms is readily available for processing records of chess games provided in online databases, Mathematica remains, somewhat surprisingly, exempt. ChessY attempts to fill this gap, by providing a simple set of tools for handling Portable Game Notation (PGN) chess records and their translation into positional chess graphs, thus opening the door for a systematic analysis of chess games within the powerful confines of graph theory using Mathematica.